Variation in genetic and environmental effects of beta-conglycinin (7S) and glycinin (11S) protein fractions in conventional and GM soybean cultivars grown in Southern Brazil - Olívio Fernandes Galão (Semina: Ciências Agrárias, 2013)
The objective of this study was to evaluate the effects of genetic and environmental variation on levels of beta-conglycinin and glycinin in commercial soybean cultivars, which were sown in showcases at Embrapa Soja, Londrina, simultaneously in Ponta Grossa, south Brazil. The concentration of protein fractions was determined by densitometry after electrophoresis in 20 cultivars, 14 conventional and 6 transgenic . We observed a significant variation as the ratio of beta-conglycinin (7S) and glycinin (11S) between the cultivars analyzed. Most 11S/7S ratios (2.21) was observed in the BRS 184, Ponta Grossa and lowest (1.31) in the BRS 233, Londrina. On average, transgenic varieties of Ponta Grossa were higher than in Londrina for both, taking into account the amount of protein fractions.